Effect of exercise therapy on established and emerging circulating biomarkers in patients with heart failure: a systematic review and meta-analysis. Issue 2 (11th July 2018) - Pearson, Melissa J; King, Nicola; Smart, Neil A
Abstract : Background: Biomarkers are important in the diagnosis, risk stratification and management of patients with heart failure (HF). The established biomarkers of myocardial stretch, brain natriuretic peptide (BNP) and amino (N) portion of BNP (NT-proBNP) have been extensively studied, and early analyses have demonstrated response to exercise training. Several other biomarkers have been identified over the last decade and may provide valuable and complementary information which may guide treatment strategies, including exercise therapy. Methods: A systematic search of PubMed, EMBASE and Cochrane Trials Register to 31 October 2017 was conducted for exercise-based rehabilitation trials in HF. Randomised and controlled trials that reported biomarkers, BNP, NT-proBNP, soluble ST2, galectin-3, mid-regional atrial natriuretic peptide, mid-regional adrenomedullin and copeptin, were included. Results: Forty-three studies were included in the systematic review, with 27 studies suitable for meta-analyses. Data pooling was only possible for NT-proBNP and BNP. Meta-analyses of conventional training studies demonstrated a statistically significant improvement in NT-proBNP (pmol/L); mean difference (MD) −32.80 (95% CI −56.19 to −9.42), p=0.006 and in BNP (pmol/L); MD −17.17 (95% CI −29.56 to −4.78), p=0.007. Pooled data of non-conventional training failed to demonstrate any statistically significant improvements. Conclusion: Pooled data indicated a favourable effect of conventional exercise therapy on the established biomarkers, NT-proBNP and BNP; however, this was in contrast to a number of studies that could not be pooled. Limited evidence exists as to the effect of exercise training on emerging biomarkers.